Potential novel therapeutic strategies for neuropathic pain - Du, Zelu; Zhang, Jian; Han, Xu; Yu, Weifeng; Gu, Xiyao (Frontiers in Molecular Neuroscience, 2023)
Purpose To explore the potential therapeutic strategies of different types of neuropathic pain (NP) and to summarize the cutting-edge novel approaches for NP treatment based on the clinical trials registered on ClinicalTrials.gov. Methods The relevant clinical trials were searched using ClinicalTrials.gov Dec 08, 2022. NP is defined as a painful condition caused by neurological lesions or diseases. All data were obtained and reviewed by the investigators to confirm whether they were related to the current topic. Results A total of 914 trials were included in this study. They were divided into painful diabetic neuropathy (PDN), postherpetic neuralgia (PHN), sciatica (SC), peripheral nerve injury-related NP (PNI), trigeminal neuralgia (TN), chemotherapy-induced NP (CINP), general peripheral NP (GPNP) and spinal cord injury NP (SCI-NP). Potential novel therapeutic strategies, such as novel drug targets and physical means, were discussed for each type of NP. Conclusion NP treatment is mainly dominated by drug therapy, and physical means have become increasingly popular. It is worth noting that novel drug targets, new implications of conventional medicine, and novel physical means can serve as promising strategies for the treatment of NP. However, more attention needs to be paid to the challenges of translating research findings into clinical practice.